Assessment of the genotoxicity of two agricultural residues after processing by diplopods using the Allium cepa assay - Christofoletti, Cintya A. [UNESP]; Pedro-Escher, Janaína [UNESP]; Fontanetti, Carmem S. [UNESP] (Springer Nature, 2013)
Agroindustrial by-products and residues from treatment of sewage sludge have been recently recycled as soil amendments. This study was aimed at assessing toxic potential of biosolid, obtained from a sewage treatment plant (STP), vinasse, a by-product of the sugar cane industry, and a combination of both residues using Allium cepa assay. Bioprocessing of these samples by a terrestrial invertebrate (diplopod Rhinocricus padbergi) was also examined. Bioassay assembly followed standards of the Brazilian legislation for disposal of these residues. After adding residues, 20 diplopods were placed in each terrarium, where they remained for 30 days. Chemical analysis and the A. cepa assay were conducted before and after bioprocessing by diplopods. At the end of the bioassay, there was a decrease in arsenic and mercury. For the remaining metals, accumulation and/or bioavailability varied in all samples but suggested bioprocessing by animals. The A. cepa test revealed genotoxic effects characterized by different chromosome aberrations. Micronuclei and chromosome breaks on meristematic cells and F1 cells with micronuclei were examined to assess mutagenicity of samples. After 30 days, the genotoxic effects were significantly reduced in the soil + biosolid and soil + biosolid + vinasse groups as well as the mutagenic effects in the soil + biosolid + vinasse group. Similar to vermicomposting, bioprocessing of residues by diplopods can be a feasible alternative and used prior to application in crops to improve degraded soils and/or city dumps. Based on our findings, further studies are needed to adequately dispose of these residues in the environment. © 2013 Springer Science+Business Media Dordrecht.
Keywords: Biosolid; Diplopods; Genotoxicity; Mutagenicity; Sugar cane vinasse; Agroindustrial by-product; Chromosome aberration; Feasible alternatives; Genotoxicities; Terrestrial invertebrate; Vinasses; Agricultural wastes; Biochemistry; Biological materials; Biosolids; Byproducts; Chromosomes; Sewage sludge; Sewage treatment plants; Soils; Sugar cane; Bioassay; arsenic; mercury; arthropod; bioaccumulation; bioassay; bioavailability; crop residue; genotoxicity; mutagenicity; sludge; soil amendment; soil degradation; soil pollution; sugar cane; waste treatment; bioprocess; bioremediation; biosolid; chemical analysis; chromosome aberration; concentration (parameters); controlled study; cytotoxicity; feasibility study; micronucleus test; millipede; nonhuman; onion; physical chemistry; residue analysis; Rhinocricus padbergi; soil analysis; vermicompost; vinasse; Allium cepa; Animalia; Diplopoda; Invertebrata; Saccharum